Logics, rationalities and contexts of the health / illness pathways of university students - Julia Maria Ribeiro Antunes (INFAD, 2016)
College students in Health Sciences are typically educated, health-conscious and are a relatively homogeneous and privileged group with respect to culture and socioeconomic status, who undoubtedly represent a great future potential for leadership that may influence with some ease other social groups at different moments of the lifecycle. In our culture and society, we find phenomenologies which we know about, but are, in fact, not easy to study, such as the medicalization of society, the phenomenon of comorbidity, iatrogenicity and quaternary prevention, additionally to all the complexity related to the medicine itself. The purpose of this study was to identify and characterize the health/disease practices of this cluster of students as well as understand the social representations of doctors, medicines and the medicine itself, developing throughout this study a theoretical subject in various degrees used to conduct this analysis. In particular, we focused in understanding if there are medicalizing practices which promote the autonomy and/or dependence of the individuals, new ways of managing the body and well-being, risk practices, self-medication, specific beliefs in regards to medicine, metaphors about medicines, as well as if there is an alignment with the quaternary prevention. 502 university students in health sciences were surveyed using a questionnaire, one of them developed by the investigator an the other by Robert Horne. The study was exploratory, descriptive study and cross-sectional. The results were subjected to a descriptive and inferential analysis, using in this case the chi-square test, factor analysis and the analysis of the main components with a significance level of (p=0,05). We found signs of common sense and critical thinking in the choices made and we found no significant differences in gender, which leads us to question: how will the Future Society be?